Low particulate carbon to nitrogen ratios in marine surface waters of the Arctic - Crawford, David W.; Wyatt, Shea N.; Wrohan, Ian A.; Cefarelli, Adrián Oscar; Giesbrecht, Karina E.; Kelly, Brianne; Varela, Diana E. (2015)
During the Canada Three Oceans and Joint Ocean Ice Study projects in the summers of 2007 and 2008, we measured particulate organic carbon to nitrogen ratios (POC:PON) throughout the euphotic zone in subarctic and arctic waters. Depth-integrated values averaged 2.65 (±0.19) in the Beaufort Sea and Canada Basin (BS-CB domain), and were much lower than both the Redfield ratio (6.6) and the average ratios (3.9 to 5.6) measured across other arctic-subarctic domains. Average uptake ratios of C and N (ρC:ρN) were also lower (0.87±0.14) in BS-CB than in the other four domains (2.10 to 3.51). Decreasing POC:PON ratios were associated with low concentrations of phytoplankton C, reduced abundance of biogenic silica (bSiO2), a smaller relative contribution of the >5 µm fraction to total chlorophyll a and a larger relative contribution of small flagellates (<8 µm) to phytoplankton C. In the subsurface chlorophyll a maximum (SCM) within the BS-CB domain, phytoplankton C represented only ~13% of POC, and therefore low POC:PON may be influenced by the presence of heterotrophic microbes. These ratios are supported by data obtained during other arctic programs in 2006, 2008 and 2009. Previous work has suggested a link between freshening of surface waters and increasing dominance of picophytoplankton and bacterioplankton in the Canada Basin, and the low POC:PON ratios measured during this study may be a consequence of this shift. Our results have ramifications for the conversion between C- and N-based estimates of primary productivity, and for biogeochemical modeling of marine arctic waters. Facultad de Ciencias Naturales y Museo